Efeito alelopático de folhas secas de Libidibia ferrea (Mart. ex Tul.) L.P. Queiroz sobre a 2 emergência, atividade da peroxidase e anatomia de raiz do milho (Zea mays L.) - Taveira, Ana Luisa Moro (2024)
Agroforestry Systems (SAFs) are sustainable production alternatives, through a consortium of tree species and agricultural crops, and studies that investigate the viability of these consortia are important. Thus, our objective was to analyze, in a laboratory environment, the allelopathic activity of Libidibia ferrea (Mart. ex Tul.) L.P.Queiroz in the germination and initial development of corn (Zea mays L.), as well as verify the allelopathic activity of the leaves of L. ferrea in corn emergence, under greenhouse conditions. Furthermore, the activity of the peroxidase enzyme and the anatomical aspects of the roots were analyzed, with the aim of verifying the possible association of these species in SAFs. To evaluate the allelopathic effect on corn germination in the laboratory, parameters such as: percentage, speed index, average time and frequency of germination of corn seeds were considered, exposed to different proportions of the aqueous extract of dry leaves of L. ferrea. Regarding initial development, the dry mass and average length of roots and aerial parts of corn seedlings were analyzed. For the emergency test in a greenhouse, the treatments were composed of different proportions of soil coverage with dry L. ferrea leaf powder, collected at 15, 30 and 45 days, after sowing, being evaluated for emergence: percentage, average time and speed index. In the initial development test in a greenhouse, seedlings collected after 15 days of sowing were used, and the dry mass of the shoot, dry mass of the root, average length of the shoot and average length of the root were evaluated. Furthermore, the activity of the peroxidase enzyme and the anatomy of the roots of seedlings collected in different periods were quantified, aiming to evaluate oxidative stress and possible structural damage to root tissues. In the laboratory, the aqueous extract of L. ferrea leaves did not influence the corn germination variables, however, it caused inhibition of the average root length. In a greenhouse, no statistical differences were observed between treatments for the variables evaluated in the emergence and initial growth of corn seedlings. There was a decrease in peroxidase activity in treatments with dry L. ferrea leaf powder, possibly indicating a reduction and control of free radicals, which alleviated stress and allowed normal plant development. The anatomical characterization of the roots did not reveal apparent structural damage in the presence of allelochemicals present in the powder of L. ferrea leaves. Despite the harmful allelopathic effect observed in the laboratory, the extract did not affect the development of corn seedlings in the greenhouse. Therefore, we suggest that consortium between species in Agroforestry Systems is viable.